(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Thyrotoxic crisis is a rare endocrine complication of pregnancy and is associated with a high risk of adverse outcomes for both the mother and the fetus. Its clinical presentation is often polymorphic and may mimic manifestations of other conditions typical of pregnancy, which frequently leads to diagnostic challenges. In this context, early diagnostic confirmation and timely involvement of a multidisciplinary team are essential to reduce maternal and perinatal morbidity. Case A 32-year-old pregnant woman at 33 weeks of gestation was admitted with complaints of abdominal pain, palpitations, excessive sweating, headache, and generalized weakness. Despite the administration of maximally intensive medical therapy, an adequate clinical response was not achieved; therefore, a multidisciplinary team consultation was conducted, and the decision was made to perform an emergency delivery. Comprehensive treatment was initiated immediately, including antithyroid medications, beta-blockers, and glucocorticoids, as well as measures aimed at preventing respiratory complications in the newborn. Conclusion This clinical case highlights the importance of timely recognition of thyroid storm, implementation of individualized treatment strategies, and strict monitoring of therapeutic adherence in pregnant patients with thyroid disorders. The presented findings contribute to the accumulation of clinical experience and may help optimize management strategies for similar patients in routine clinical practice. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 1014-1022